Organizational ecology - Hannan, Michael T. (Harvard University Press, 1993)
Hannan and Freeman examine the ecology of organizations by exploring the competition for resources and by trying to account for rates of entry and exit and for the diversity of organizational forms. They show that the destinies of organizations are determined more by impersonal forces than by the intervention of individuals.